Eating disorderes in patients with diabetes - Krzymień, Janusz; Kryńska, Łucja (Przewodnik Lekarza/Guide for GPs, 2005)
Bulimia nervosa, anorexia nervosa, eating disorders not otherwise specified are seen more often in diabetic patients than in non-diabetic population (7-14% vs 1,5-4%). Factors inducing eating disorders in diabetic patients include: constant focusing on diet, weight, and self-control, increase of weight in first year of insulin treatment, frequent depression and fear syndromes, low self-esteem and feeling of being unattractive, feeling of guilt after breaking the diet rules. The need for multiple hospitalizations due to metabolic decompensations and difficulties in obtaining proper glycogenic control in hospitalized patients may reflect underlying psychogenic eating disorders. Detailed history of pathologic behaviors may help in making correct diagnosis.